Strengthening the Performance of Micro and Small Industries in Mojokerto City: Antecedents of Management Orientation and Business Innovation - Prawira, Yuda; Iriantini, Dwi Bhakti (LPPM of NAROTAMA UNIVERSITY, 2025)
Objective: This study aims to examine the effect of management orientation on business innovation and business performance enhancement, as well as the effect of business innovation on business performance enhancement in micro and small industries. Design/methodology/approach: This study is categorized as quantitative research with an associative/explanatory approach accompanied by hypothesis testing. The unit of analysis in this study was micro and small industry business actors with a population of 163. The sample size in the study was 84 (51,53%), and the sample members were taken from the population using purposive sampling, which was then referred to as respondents. The questionnaire was distributed over a period of four weeks (August 1, 2025 - August 28, 2025) and was filled out by several respondents; therefore, the data collected through this questionnaire is quite representative of the population. Findings: Testing in path analysis shows that management orientation directly and significantly affects business innovation and business performance, strengthening with standardized coefficient values of 0,316 (sig. 0,046) and 0,394 (sig. 0,039), respectively. While business innovation directly and significantly affects the strengthening of micro and small business performance, with a standardized coefficient value of 0,317 (sig. 0,043). The results of this study indicate that a management orientation that is responsive to change and adaptive to environmental changes will spur creative behavior in business innovation, thereby creating effective and efficient business practices in managing resources and encouraging better business performance. Business innovation that focuses on the use of digital platforms and social media is able to provide services to consumers more quickly, easily, and flexibly without being limited by time, place, and space, thereby encouraging the strengthening of business performance. Strengthening the performance of micro and small industries can be achieved when management is more responsive to environmental changes and able to implement them in business processes, increasing creativity in carrying out business innovation effectively and efficiently, both in business management, applying management functions, and business cycles. Strengthening management orientation and business innovation can be relevant antecedents to explain the strengthening of the performance of micro and small industries. Therefore, hypotheses H1, H2, and H3 can be accepted because all the antecedents tested have a direct, positive, and significant effect with a significance level below 0.05.